LOSS OF ARID 1A PROTEIN EXPRESSION IN OVARIAN ENDOMETRIOMAS AS A PROBABLE PREDISPOSITION TO DEVELOPMENT OF ENDOMETRIOSIS-ASSOCIATED OVARIAN CARCINOMAS - Tihomir Totev; Grigor Gorche; Slavcho Tomov (Peytchinski Publishing, 2019)
Purpose: The aim of the study was to establish a loss of ARID 1A protein expression in cases of ovarian endometriomas and its probable role in the development of clear-cell and endometrioid ovarian carcinomas. Material and Methods: The immunohistochemical analysis of ARID 1A protein expression was performed on specimens collected from the study group (group 1) that included 72 patients with endometrioid ovarian cysts. The control group (group 2) included 15 patients with clear-cell and endometrioid ovarian carcinomas. Results: In the study group, 1 of 72 specimens (1,4%) showed a complete absence of reactivity and was defined as ARID 1A protein deficient. In the control group, 5 of 15 specimens (33.3%) were found to be ARID 1A protein deficient. In 7 (46.7%) cases of this group, together with the malignant component adjacent endometriosis was diagnosed. Two of these endometrioses were atypical, with an ARID 1A protein deficient expression. Conclusions: These data confirm the hypothesis that in some endometriomas mutation of the tumor-suppressor ARID 1A gene occur, leading to the loss of protein expression and its functional activity, thus indicating a high risk for the development of endometriosis-associated ovarian cancer.